Raising Awareness to Empower Voices: Applying a Consciousness-Raising Approach to English Presentation Skills - Rizdika Mardiana; Dewi Utami; Nurrahma Restia Fatkhiyati; Jeffrey Dawala Wilang (JET (Journal of English Teaching), 2026)
This study explores how a consciousness-raising (C-R) instructional approach enhances linguistic awareness, strategic preparation, and confidence in English presentation tasks among Indonesian high school students. Grounded in Ellis’ (2002) and Widodo’s (2008) framework, the six-step C-R speaking plan guided thirty Grade 12 students through noticing, analyzing, reformulating, and performing structured presentations. Data were collected through semi-structured interviews and written reflections and analyzed using Braun and Clarke’s (2006) thematic analysis. Five themes emerged such as linguistic and cognitive awareness, emotional responses to speaking, strategic coping and learning efforts, performance pressure and learning contexts, and motivation and future orientation. The findings highlight the transformative potential of C-R instruction in bridging language awareness and communicative practice. Implications are offered for integrating C-R pedagogy into EFL speaking courses.